Learning Needs of Youth With Type 2 Diabetes. (May 2013) - Richards, Denise; Larkin, Mary; Milaszewski, Kerry; Javier, Elaine; Casey, Terri; Grey, Margaret
Purpose: The purpose of this study was to examine reports of diabetes learning needs by youth with type 2 diabetes and their family support person (FSP) and to examine correlations of these perceptions with demographic variables. Methods: Data were analyzed from the Participant Needs Assessment (PNA), a routinely self-administered questionnaire designed to assess learning needs, in 191 youth (mean age = 14.0 ± 1.9 years, duration 8.78 ± 6.30 months; 36% black, non-Hispanic; 40% Hispanic; 20% white) enrolled in the TODAY (Treatment Options for Type 2 Diabetes in Adolescents and Youth) study. Youth and their FSPs completed the PNA at scheduled study visits, rating their learning needs on a 5-point scale, with higher scores indicating higher needs. Paired t tests and ANOVA were used. Results: There were no differences in reported learning needs by gender, although scores on the Teen Issues scale approached significance, with girls reporting higher needs than boys. Youth and FSPs were similar on their reports of needs on 3 scales (Ordinary Day, Nutrition, and Living With Diabetes), but youth reported higher needs than FSPs on Focus and Teen Issues. Controlling for duration of diabetes, these differences between youth and FSPs persisted. In general, learning needs for both youth and FSPs decreased over time. Conclusions: Youth with type 2 diabetes and their FSPs have high levels of ongoing learning needs despite completion of a standard diabetes education program. Continued assessment of learning needs, follow-up education, and behavioral approaches are warranted for these high-risk youth.